Effect of dislocations in relaxed MBE SiGe layers on the electrical behavior of Si/SiGe heterostructures - Horvath, Zs.J.; Orlov, L.K.; Ivina, N.L.; Demidov, E.S.; Vdovin, V.I.; Adam, M.; Szabo, I.; Dozsa, L.; Pashaev, E.M.; Ivanov, Yu.M.; Yakunin, S.N. (Functional Materials, 2004)
Defects in Si/SiGe heterostructures and electrical behavior thereof have been studied. Misfit dislocations were observed in the epitaxial layers using cross-sectional transmission electron microscopy. These defects cause anomalies in the electrical behavior. It has been shown that, in spite of anomalies, the electrical measurements provide useful and reliable information on the structures. Исследованы дефекты в гетероструктурах Si/SiGe и их электрические характеристики. В эпитаксиальных слоях методом просвечивающей электронной микроскопии поперечных сечений обнаружены дислокации несоответствия. Эти дефекты вызывают аномалии в электрических характеристиках. Показано, что, несмотря на эти аномалии, электрические измерения обеспечивают полезную и надежную информацию о структурах. Досліджєно дефекти у гетероструктурах Si/SiGe та їх єлєктричні характеристики. В епітаксиальних шарах методом просвічувальної електронної мікроскопії поперечних перерізів виявлено дислокації невідповідності. Ці дефекти спричиняють аномалії в електричних характеристиках. Показано, що, незважаючи на ці аномалії, електричні вимірювання забезпечують корисну та надійну інформацію про структури.